Guide to the Senate - Pastrana, Reginald M. (Legislative Research Service, 1998)
Purpose: "...to provide a broad overview of the organization and composition of the Senate as well as its unique roles and functions. In particular, it also attempts to give insights on knowing fully how the senate works as an institution, essentially in matters of legislation and other non-legislation functions."